The Supply Side of Household Finance - Foà, Gabriele; Gambacorta, Leonardo; Guiso, Luigi; Mistrulli, Paolo Emilio (Review of Financial Studies, 2019)
Using matched borrower-lender data, we document strong nonprice supplier effects in mortgage contract choice. For given relative price of adjustable and fixed rate mortgages, households borrowing from banks hit by shocks to the cost of long term funding, or to the deposits base or to access to securitization are more likely to choose adjustable rate mortgages. Supply factors have larger effects on less-sophisticated households and at times of price inaction. A model in which banks affect borrowers’ choices through prices and distorted advice predicts these findings. We contrast the distorted advice interpretation of the evidence against the potential alternative nonprice channels. Received April 7, 2017; editorial decision October 21, 2018 by Editor Stijn Van Nieuwerburgh. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.